Identification of genetic variants in five chinese families with keratoconus: Pathogenicity analysis and characteristics of parental corneal topography - Cheng, Wan-Yu; Yang, Shang-Ying; Huang, Xiao-Yu; Zi, Fei-Yin; Li, Hui-Ping; Sheng, Xun-Lun (Frontiers in Genetics, 2022)
Purpose: The purpose of the study is to identification genetic variants in five Chinese families with KC and describe the characteristics of parental corneal topography. Methods: Fifteen participants including five probands and ten parents from five Chinese families with keratoconus were recruited in genetic and clinical analyses. Targeted next-generation sequencing using a custom designed panel for KC was applied on the probands for variant identification. Sanger sequencing and cosegregation analysis of the suspected pathogenic variants were performed with the family members. The pathogenicities of variants were evaluated according to the American College of Medical Genetics and Genomics guidelines (ACMG). Pentacam 3D anterior segment analysis system was applied for keratectasia detection and the Corvis ST for corneal biomechanics measurement. 15 parameters were recorded, including 9 indicators of keratectasia (BAD-D, TP, Kmax, Df, Db, Dp, Dt, Da, ARTH), 6 corneal biomechanical indicators (CBI, DA ratio, SP-A1, IR, bIOP,TBI). Results: A total of six novel variants, including 5 missense variants and 1 frameshift variants, were detected in the HMX1, SLC4A11, TGFBI, PIKFYVE, and ZEB1 genes in 5 probands, all of which showed co-segregation of genotype and clinical phenotype and were determined to be pathogenic. The genetic model was autosomal dominant (AD) in 4 families and autosomal recessive (AR) in 1 family. The analysis of keratectasia and corneal biomechanical indicators of the proband’ parents (first-generation relatives) in AD families revealed that there were several abnormal indexes in BAD-D, TP, Kmax, Df, Db, Dp, Dt, Da, CBI, DA ratio, SP-A1, IR, bIOP and TBI test indexes, showing clinical characteristics of incipient KC. Conclusion: Our study provide evidence that variants in HMX1, SLC4A11, TGFBI, PIKFYVE and ZEB1 genes were associated with KC. The clinical phenotype of autosomal dominant KC showed irregular dominant inheritance, in which different individuals in the same family carried the same pathogenic heterozygous variants, but the severity of corneal morphological changes was different. Our study is the first investigation identify genetic variants and contrast the characteristics of parental corneal topography in Chinese families. Our study extends the gene spectrum associated with KC and provide novel insights into phenotypic assessments of KC, and contribute.